Semantic Study and Learning Implementation in Surah Al ‘Alaq - Syamsudin Syamsudin (International Journal of English Learning and Applied Linguistics (IJELAL), 2022)
The Qur'an as the holy book of Muslims, of course, has many interpretations of verses, including the content of verses discussing education. One of the letters and verses of the Qur'an that discusses education is Surah al-'Alaq verses 1-5, which refers to science, namely by ordering reading as the key to knowledge. The command to 'read' in that verse is called twice an order to the Messenger of Allah, and then an order to all his people. Reading is one of the keys to science, both etymologically in the form of reading literature written in books, as well as terminologically, namely reading in a broader sense, meaning reading the universe (verse al-kauniyah). Seeking knowledge is a commandment for every Muslim, male and female, in addition to the basic knowledge, namely syar'i science, including the pursuit of science and technology, this is clearly seen in the verse that was first revealed with the word iqra' , whose meaning includes all knowledge, both the knowledge of the world and the science of the hereafter. However, the generality of the iqra' command is muqayyad (interrelated), not absolute, so that seeking knowledge that is justified by the Shari'ah is on the condition of 'bismi Rabbik' (in a way that is justified by the Lord). This research is to explore the values contained in surah al-'Alaq verses 1 to 5, which focuses on the science of education. After deciphering the meaning of words in the verses of Surah all-'Alaq verses 1 to 5, it was found that at least 3 (three) educational values were found, namely: skill values, divine values and intellectual values (reason).